Propagación y análisis del crecimiento en genotipos promisorios o potenciales de chirimoya (Annona cherimola Mill.) en la provincia de Loja. - Cajilima Ponce, Johanna Mishell (2024)
Cherimoya, a species of great cultural and nutritional value, requires conservation to preserve its biodiversity and unique characteristics. This study evaluated vegetive propagation through grafting, using disinfection procedures and the application of growth regulators and biostimulants to assess their effects on graft success and initial growth. Cherimoya scions were collected from five cantons in Loja (Gonzanama, Calvas, Paltas, Espindola, Saraguro) and treated with the fungicide Captan, a growth regulator (Auxin-ANA), and a biostimulant (Ascophyllum nodosum seaweed extract). The treated scions were then grafted using terminal cleft grafting technique. Variables such as graft success, days to first sprouting, percentage of buds emerged per scion, shoot length, chlorophyll content, leaf area, and number of leaves were measured. The results showed that scions disinfected in the initial growth variables. In conclusion, the terminal cleft grafting technique combines with disinfection of plant material resulted in high graft growth for the variables measured.